Formadores de formação continuada de professores: aprendizagem e desenvolvimento profissional em uma perspectiva heutagógica - Santos, Jussara Gabriel dos (2022)
This thesis is part of the research developed in the Postgraduate Program in Education (Doctorate degree) at the Federal University of São Carlos (UFSCar), in the Teacher Education and other Educational Agents research group. It deals with learning and professional development of teacher educators working in the field of continuing education for teachers, specifically in training centers. In general, teacher educators are people who are involved in the formative processes of other teachers. Continuing education is understood as a professional right of teachers and should be guaranteed by the State. In Uberlândia city, in the state of Minas Gerais in Brazil, the initiatives in this regard are under the responsibility of the Julieta Diniz Municipal Center for Educational Studies and Projects (In this thesis it is used the acronym “CEMEPE” which refers to the Brazilian institution’s name: Centro Municipal de Estudos e Projetos Educacionais Julieta Diniz). The professionals who propose the training in this organization are mostly teachers from the municipal education system itself. Thus, there is an interest in understanding the formative processes of these professionals triggered in the function of teacher’s educators. The general objective is: to analyze the learnings of the teacher educators who worked in the continuing education of the Cemepe and their unfoldings for professional development. Besides, as specific objectives we highlight the following ones: to analyze the construction of learning and professional development occurred in the experience of Cemepe's teacher educators; to understand the formative processes of the educators through personal and professional trajectories; and to identify the personal and professional dimensions involved in the learning and professional development of them. In order to accomplish such objectives, we take as subsidy the heutagogy perspective which is an approach to adult learning (HASE; KENYON, 2013; BLASCHKE; KENYON; HASE, 2014), the learning experience as a fundamental unit of analysis (LARROSA, 2014) and the data are considered from the point of view of three teacher educators who worked in Cemepe. In complementarity with the heutagogy we adopted the characteristics of the qualitative approach (BOGDAN; BIKLEN, 1994), the semi-structured interview as a data collection instrument (LEITE, 2008; MINAYO, 2015; MARCONI, 2010; OLIVEIRA, 2012) and thematic content analysis as a form of data treatment (FRANCO, 2005; GOMES, 2015). The results allowed us to conclude that it is in the daily exercise of the function of trainer that the construction and expansion of learning occurs, with the trainers being the main conductive agents. The situated learnings are linked to life and professional trajectories, which, in turn, personify the formation and shape the performance of the trainers. Emotions, beliefs, experiential knowledge, and pedagogical tact are the most expressive personal and professional dimensions in the formative processes. The formative processes are contextually informal, ecological, naturally heutagogical, and have double-loop learning as their central axis. The relationship between learning and professional development takes on a continuum throughout life, because they have been identified at different moments in the trainers' careers. Thus, the concept of longitudinality of the professional development of the trainer was coined, being the sum of previous learning, situated and reverberated in different contexts in the professional career of the trainers.